ACADEMIC PERSONNEL COMPETITION ACADEMIC SECTION HEAD OFFICE OF SAM RATULANGI UNIVERSITY - PANGALILA, IRENE; POSUMAH, JOHNNY HANNY; RURU, JOORIE MARHAEN (Sam Ratulangi University, 2018)
The University of Sam Ratulangi Manado is also supported by the presence of educational personnel.Headquartered at the University of Sam Ratulangi Manado, there is the Academic and Student AffairsBureau. Under the academic bureau, there is an Academic Section that serves the community especiallystudents. Academic activities, such as admission of new students, re-enrolment of freshman students whenthey have been graduated as Unsrat students, graduation, and others. These activities are done by educationalstaff.The purpose of this study is to determine the competence of educational personnel viewed from aspects ofknowledge, skills, self-concept, personal characteristics, and motives of employees in the Academic DivisionSam Ratulangi University Head Office in carrying out its work duties. The method used is qualitative methodand data analysis technique is descriptive. Data collection techniques are observation, interview anddocument while informant of research done by using purposive sampling.From this study obtained the conclusion that the competence of education staff Academic Section HeadOffice of Sam Ratulangi University has been done. This can be seen based on indicators presented by Spencerand Spencer that is knowledge, skills, self-concept and values, personal characteristics and motives. But forindicators of knowledge and skills of employees require education and training to hone knowledge and skillspossessed.Keywords: Competency, Academic Personnel